The relation of infectious and inflammatory markers with placental atherosclerosis in preeclampsia - Esra Ozkaplan, Sukran; Emre Topdagi, Yunus; Ustun, Yusuf (Annals of Medical Research, 2021)
Aim: The aim of this study was to compare CRP, TNF-α, CMV, Chlamydia pneumonia IgG and IgM levels between preeclamptic and uneventful pregnant womens, to explain the effects of infectious trigger on the placental pathology of preeclampsia. Materials and Methods: All cases of preeclamptic pregnants detected at or referred to Inonu Univrsty Faculty of Medicine Gynaecology and Obstetric Department between July 2006 and July 2007 were prospectively collected. The study group was a group of 40 women who are preeclamptic. The study also included 40 control subjects who were matched for age, gestational age and body mass index. Results: In the preeclamptic group the level of CRP was significantly higher [28 (1.9– 196); vs. 6.2 (1.2–23) (mg/L) (p0.999 and p=0.385). Plasma H.pylori IgA levels were higher in the study group with the value of [ 14 (35%) vs. 5 (12.5%) (p=0.035)].Conclusion: In the present study, serum CRP, TNF-α and H.pylori IgA levels were significantly higher than normal pregnant women.